Influence of NCF architecture on the morphology of forming induced wrinkling - Jimenez Martin, Claudia; Maes, Vincent K.; McMahon, Turlough; Kratz, James (Frontiers in Materials, 2023)
Biaxial Non-Crimp Fabrics (NCFs) offer the high deposition rates needed to meet the increased production rate targets of the aerospace industry, but formability remains an issue for complex parts. In this study a large scale, complex geometry with a span of 2 meters is used to study wrinkle patterns in NCF preforms and how they are influenced by several key NCF parameters. Wrinkle dimensions are captured in 3D scans and used as a proxy metric for ‘formability’. Results show that whereas location and shape of the wrinkling are driven by geometry, wrinkle size and its metrics (amplitude, wavelength, aspect ratio) are driven by the NCF architecture. In addition, conflicting trends on wrinkle size observed show the complexity of forming as a process. The results presented show the importance of using several characterisation methods and not reducing wrinkling characterisation to a single data point or set.